DEVELOPMENT OF SMARTBOOK LEARNING MEDIA FICTIONAL STORY MATERIAL BASED ON EAST JAVA FOLK STORIES FOR CLASS 4 PRIMARY SCHOOL STUDENTS - Kristianto, Johanes Victory; Hunaifi, Abdul Aziz; Santi, Novi Nitya (Universitas Labuhanbatu, 2023)
This research is motivated by teachers still using the teacher center method so that learning is monotonous and the learning media is less interesting. Apart from that, it is not effective because students are less enthusiastic about learning so that learning outcomes are not satisfactory. This research has an urgency, namely to make learning interesting, innovative and make students have more motivation and enthusiasm for learning. The solution to overcome the problem is to develop learning media, namely smartbooks. The aims of the research are: (1) to determine the validity of smartbook learning media, (2) to determine the practicality of smartbook learning media, (3) to determine the effectiveness of smartbook learning media. This research is a type of development research (R&D) using a 4D development model through stages: (Define), (Design), (Development), and (Disseminate). The define stage is used to analyze and find out needs in the school. The design stage is to determine and design the product being developed. The development stage of the final product is different from other products. The disseminate stage is used for the product dissemination process through validation. The conclusion of this research: smartbook learning media is said to be very valid with a percentage of 86%. The results of the learning media teacher responses were said to be very practical with a percentage of 94%. Smartbook learning media is said to be very effective because after limited trials it got a percentage of 91% and extensive trials got 88%.Keywords: Smartbook Learning Media; fictional stories; East Javanese folklore.Abstrak Penelitian ini dilatarbelakangi oleh guru masih menggunakan metode teacher center sehingga pembelajaran monoton dan media pembelajaran kurang menarik. Selain itu tidak efektif karena siswa kurang bersemangat belajar sehingga hasil belajar belum memuaskan. Penelitian ini memiliki urgensi yaitu guna membuat pembelajaran menjadi menarik, inovatif dan membuat siswa memiliki motivasi serta semangat belajar yang lebih. Adapun solusi untuk mengatasi permasalahan ialah mengembangkan media pembelajaran yaitu smartbook. Tujuan dari penelitian ialah: (1) untuk mengetahui kevalidan media pembelajaran smartbook, (2) untuk mengetahui kepraktisan media pembelajaran smartbook, (3) untuk mengetahui keefektifan media pembelajaran smartbook. Penelitian ini termasuk jenis penelitian pengembangan (R&D) menggunakan model pengembangan 4D melalui tahapan: (Define), (Design), (Development), dan (Disseminate). Tahap define digunakan menganalisis dan mencari tahu kebutuhan di sekolah. Tahap design guna menentukan dan merancang produk yang dikembangkan. Tahap Development hasil final produk berbeda dengan produk lain. Tahap disseminate digunakan guna proses penyebaran produk melalui validasi. Kesimpulan penelitian ini: media pembelajaran smartbook dikatakan sangat valid dengan presentase sebesar 86 %. Hasil dari respon guru media pembelajaran dikatakan sangat praktis dengan presentase sebesar 94%. Media pembelajaran smartbook dikatakan sangat efektif sebab setelah uji coba terbatas mendapatkan presentase sebesar 91% dan suji coba luas mendapatkan 88%.Kata Kunci: Media Pembelajaran smartbook: cerita fiksi: cerita rakyat Jawa Timur